Molecular Risk Factors for Thrombosis - Bertina, Rogier M. (Thrombosis and Haemostasis, 1999)
A diagnosis of venous thrombosis is made each year in about 0.1% of Western populations. In the majority of cases, the diagnosis is based on objective evidence for an obstruction of the circulation by a blood clot that either formed locally or developed elsewhere in the circulation. The interest in the pathogenesis of this hemostatic process has increased enormously during the past 20 years and, as a consequence, substantial progress has been made in understanding the multifactorial nature of the disease, where interactions between genetic and environmental factors result in the formation of an obstructive thrombus at a specific time and at a specific location. Frequently, these thrombi are found in the elderly in the superficial and deep veins of the legs. Thrombi may also occur in younger individuals and in the veins of the brain, mesentery, liver, or retina.The episodic nature of the disease points out the importance of acquired and/or environmental factors in thrombosis. The disease also has strong genetic components, given the many reports of familial clustering of thrombotic events1-3 and the fact that 20% to 30% of patients with a first thrombotic event report at least one first-degree relative with thrombosis.4The search for molecular risk factors for venous thrombosis remains intensive. Over the years, this research has been facilitated by new insights in the regulation of blood coagulation and by the development of new research methods, especially in the field of molecular genetics. Today, at least one genetic defect can be found in about 70% of the families with thrombophilia.5Initial studies focussed on patients and their relatives (family studies). Such studies are very useful but can be hampered by selection bias. In other words, we know these families because the proband and some of his/her relatives have experienced thrombosis. Therefore, later studies used groups of unrelated patients and healthy controls (patient-control studies). One of the limitations of these studies is that they need to be very large to identify the less common risk factors.The concept of venous thrombosis as a multifactorial disease has received much attention in recent years.6-8 One of the reasons is that some of the newly discovered genetic risk factors concern single point mutations that are quite common in the general population (e.g., factor V Leiden, prothrombin 20210A allele).9,10 As a result, studies focussing on the interaction of these mutations with other relatively common risk factors (e.g., use of oral contraceptives,11,12 pregnancy,13 surgery,14 but also lupus anticoagulant15 or mild hyperhomocysteinemia16,17) have become feasible. In addition, researchers will continue to learn more about the relationship between these common molecular risk factors and the clinical phenotypes, namely deep vein thrombosis, pulmonary embolism, superficial thrombosis, and first versus recurrent events.